Challenges in Cytomegalovirus (CMV) Retinitis Management - Denisa Rosati; Sauli Ari Widjaja; Wimbo Sasono; Muhammad Firmansjah; Ima Yustiarini; Ady Dwi Prakosa; Moestidjab Moestidjab; Gatut Suhendro (International Journal of Retina, 2019)
Introduction: HIV infection can manifest in a variety of ways in and around the eyes and it is most commonly due to retinal microvasculopathy, neoplasm and also opportunistic infection. Those usually occur associated with a significantly reduced CD4 T-cell counts. In this era of Highly Active Anti Retroviral Therapy (HAART) has caused a major decreasing of the ocular involvement prevalence itself. Case presentation : A 31 year-old-male came with blurred vision on the right eye, which has started 3 years ago and slowly worsened. Central scotoma also presented previously. Patient was an HIV-AIDS, that placed him on HAART. CD4+ T-lymphocyte count was 3 cells/mm3. The initial visual acuity was light perception and fundus examination showed Roth spots, massive exudates and hemorrhages covering the optic disc and decreased foveal reflex. Laboratory examination revealed positive Rubella and anti-CMV immunoglobulin-G (IgG). He also suffered from lung tuberculosis and took tuberculosis medication regularly. Patient was diagnosed with Cytomegalovirus (CMV) retinitis based on history of illness, fundus examination as well as laboratory testing and given oral induction valganciclovir 900 mg once daily for 3 weeks followed by maintenance dosage . Result : After valganciclovir induction, there was significant changes with decreased peripapillary exudates, hemorrhages and vasculitis, but the optic disc appeared pale. The patient also had bicytopenia due to valganciclovir therapy that complicate his condition and passed away after 3 months follow up. Conclusion: CMV retinitis is reported to occur in patient with extreme CD4 count usually less than 50 cells/mm3. The sooner of proper treatment would likely following better outcome. Making diagnosis of immunosuppresed patient with ocular manifestations was challenging so that comprehensive eye examination in HIV-infected individuals should be conducted. Oral valganciclovir could give satisfactory response to decrease the progression of retinitis but risk of blindness may still occur.